The Effect of Station Technique Used in Science and Technology Class on Students’ Achievement and Retention - İbrahim Benek and Serhat Kocakaya (Elementary Education Online, 2023)
In this study, the effect of station technique used in Science and Technology course on students’ achievement and retention investigated. The research was conducted with 79 students in the 7th grade from two different primary schools located in the east of Turkey on the 2nd term of 2010-2011 educational year. For the study, an experimental group and two control groups were randomly selected by the researchers. The research was conducted according to the pretest-posttest model with control group. During the application process, the students in the experimental group were learning the subjects by station technique while the students in the control groups were learning the subjects by the activities planned in the science and technology course curriculum. In this study, an "Optics Achievement Test" consisting of 23 multiplechoice questions was developed by the researchers to measure changes in student achievement, and this test was applied to all groups as pretest and posttest. Also 6 weeks after posttest, "Optics Achievement Test" was reapplied to experimental group as retention test. According to the findings, it is concluded that station technique is more effective than existing curriculum activities on students’ achievement, and it enables retention of the learnt subjects (p<0.05). In addition, in this study, John Henry, and Hawthorne effects, the most important factors threatening internal validity in experimental studies, were tried to be controlled.